PENGARUH SUPPORT SYSTEM DAN WORK LIFE BALANCE TERHADAP PENGEMBANGAN KARIER DAN KEPUASAN KERJA PEGAWAI WANITA DI YAYASAN DHYANA PURA - Kadek Fransiska Kharisma Oktarina; Yeyen Komalasari; Gusti Ngurah Joko Adinegara; Christimulia Purnama Trimurti (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to determine the influence of support systems and work-life balance on career development and job satisfaction among female employees at Yayasan Dhyana Pura. The research methodology employed a quantitative approach. The sample consisted of all female employees at Yayasan Dhyana Pura totaling 37 individuals. Data collection techniques included questionnaires, interviews, observations, and literature reviews. The analytical techniques utilized to address the hypotheses were quantitative descriptive analysis and Partial Least Square (PLS) using a Structural Equation Modeling (SEM) framework. The findings indicate that support systems have a positive influence on the career development and job satisfaction of female employees at Yayasan Dhyana Pura. Although work-life balance does not significantly affect either, career development positively impacts job satisfaction, and the presence of a strong support system enhances career development opportunities, thereby increasing job satisfaction, while work-life balance has no direct influence.